The Importance of the Water Inventory Card - Ibragimov Lazizbek Toshpulat ogli; Akaboev Jasur Abdugapporovich (International Journal on Orange Technologies, 2021)
The use of thematic and complex maps in the preparation of maps of the water cadastre of the republic, water resources management, planning is one of the most convenient tools in this regard. It is argued that their creation requires the use of modern geographic information systems (GIS).